Roman Transport Network Connectivity and Economic Integration - Matthias Flückiger; Erik Hornung; Mario Larch; Markus Ludwig; Allard Mees (Center for Economic Studies and ifo Institute (CESifo), 2019)
We show that the creation of the first integrated pan-European transport network during Roman times influences economic integration over two millennia. Drawing on spatially highly disaggregated data on excavated Roman ceramics, we document that interregional trade was strongly influenced by connectivity within the network. Today, these connectivity differentials continue to influence cross-regional firm investment behaviour. Continuity is largely explained by selective infrastructure routing and cultural integration due to bilateral convergence in preferences and values. Both plausibly arise from network-induced history of repeated socio-economic interaction. We show that our results are Roman-connectivity specific and do not reflect pre-existing patterns of exchange.
Keywords: F14; F15; F21; N73; R12; R40; O18; 330; economic integration; Roman trade; transport network connectivity; business links; cultural similarity